Tracking the distribution, genetic diversity and lineage of Brucella melitensis recovered from humans and animals in Egypt based on core‐genome SNP analysis and in silico MLVA‐16. Issue 6 (28th November 2022) - Holzer, Katharina; Wareth, Gamal; El‐Diasty, Mohamed; Abdel‐Hamid, Nour H.; Hamdy, Mahmoud E. R.; Moustafa, Shawky A.; Linde, Jörg; Bartusch, Felix; Abdel‐Glil, Mostafa Y.; Sayour, Ashraf E.; Elbauomy, Essam M.; Elhadidy, Mohamed; et al.
Abstract: Brucellosis is one of the most common neglected zoonotic diseases globally, with a public health significance and a high economic loss in the livestock industry caused by the bacteria of the genus Brucella . In this study, 136 Egyptian Brucella melitensis strains isolated from animals and humans between 2001 and 2020 were analysed by examining the whole‐core‐genome single‐nucleotide polymorphism (cgSNP) in comparison to the in silico multilocus variable number of tandem repeat analysis (MLVA‐16). Almost all Egyptian isolates were belonging to the West Mediterranean clade, except two isolates from buffalo and camel were belonging to the American and East Mediterranean clades, respectively. A significant correlation between the human case of brucellosis and the possible source of infection from animals was found. It seems that several outbreak strains already existing for many years have been spread over long distances and between many governorates. The cgSNP analysis, in combination with epidemiological metadata, allows a better differentiation than the MLVA‐16 genotyping method and, hence, the source definition and tracking of outbreak strains. The MLVA based on the currently used 16 markers is not suitable for this task. Our results revealed 99 different cgSNP genotypes with many different outbreak strains, both older and widely distributed ones and rather newly introduced ones as well. This indicates several different incidents and sources of infections, probably by imported animals from other countries to Egypt. Comparing our panel of isolates to public databases by cgSNP analysis, the results revealed near relatives from Italy. Moreover, near relatives from the United States, France, Austria and India were found by in silico MLVA.